Environmentally Adaptable and Temperature‐Selective Self‐Healing Polymers. Issue 24 (2nd November 2018) - Ju, Sung Hwan; Kim, Jin Chul; Noh, Seung Man; Cheong, In Woo
Abstract: Development of polymeric materials capable of self‐healing at low temperatures is an important issue since their mechanical strength and self‐healing performance are often in conflict with each other. Herein, random copolymers with self‐healing capability in a wide temperature range prepared from 2‐(dimethylamino)ethyl methacrylate (DMAEMA), glyceryl monomethacrylate (GlyMA), and butyl methacrylate monomers via free‐radical polymerization and subsequent cross‐linking with hexamethylene diisocyanate are reported. Wound closure is facilitated by swelling below the lower critical solution temperature or by heating above the glass transition temperature ( T g ) of the polymer. GlyMA units form metal–ligand coordination complexes with dibutyltin dilaurate, leading to the formation of new carbonate bonds under ambient CO2 and H2 O conditions. Although swelling/heating reduces the polymer's mechanical strength, it is fully restored following chemical re‐bonding/drying at room temperature. The swelling and degree of scratch healing are affected by pH, temperature, and the DMAEMA content. Abstract : Self‐healing polymers at low temperatures below the glass transition temperature are limited. This study reports the design and characterization of self‐healing polymers having combinatory lower critical solution temperature and catalytic carbonation bond formation capability for low‐temperature wound healing under ambient conditions.